The NOvA DAQ Monitor System. Issue 8 (December 2015) - Baird, Michael; Grover, Deepika; Kasahara, Susan; Messier, Mark
Abstract: The NO v A (NuMI Off-Axis v e Appearance) experiment is a long-baseline neutrino experiment designed to search for vµ ( v̅µ ) to v e ( v̅ e ) oscillations using Fermilab's NuMI main injector neutrino beam. The experiment consists of two detectors; both positioned 14 mrad off the beam axis: a 220 ton Near Detector constructed in an underground cavern at Fermilab and a 14 kton Far Detector constructed in Ash River, MN, 810 km from the beam source. The health and performance of the NO v A Data Acquisition (DAQ) system is monitored with a DAQ Monitor system based on the Ganglia distributed monitoring system, an open source third-party product which provides much of the NO v A DAQ monitoring needs "out-of-the-box". This paper will discuss the use of the Ganglia system for this purpose, including augmentations we have made to the Ganglia base for the specific needs of our system. This paper will also discuss two other systems used to monitor the quality of the data collected by the NO v A detectors: an Online Monitoring system and Event Display, both of which leverage tools from the offline framework to provide close to real time diagnostic tools of detector performance.